Lymphocyte changes in beta-thalassaemia major. Issue 12 (December 1979) - Musumeci, S; Schiliro, G; Romeo, M A; Sciotto, A; Rosalba, A; Pizzarelli, G
Abstract : Lymphocyte subpopulations were studied in 20 hypertransfused patients with beta-thalassaemia major, some of whom had been splenectomised. B-lymphocytes were normal but T-lymphocytes were decreased in all patients. The T-cell count was lower in the splenectomised patients than in the nonsplenectomised ones. In the former, the active rosette-forming lymphocytes were also diminished, but the difference was not significant. In all patients the percentage of null cells was greater and the activity of K-cells increased compared with controls.